2018
DOI: 10.4049/jimmunol.1800275
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Combines Effectively with Anti–PD-L1 Treatment and Can Augment Antitumor Responses

Abstract: Immunotherapy with checkpoint inhibitors has proved to be highly effective, with durable responses in a subset of patients. Given their encouraging clinical activity, checkpoint inhibitors are increasingly being tested in clinical trials in combination with chemotherapy. In many instances, there is little understanding of how chemotherapy might influence the quality of the immune response generated by checkpoint inhibitors. In this study, we evaluated the impact of chemotherapy alone or in combination with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…Indeed, our study showed an enhanced efficacy of anti-PD-1 administration plus DOX chemotherapy in reducing the growth in PyMT tumors compared to monotherapy. In line with our findings, preclinical studies demonstrated the efficacy of anti-PD-(L)1 plus different chemotherapy agents in murine colon and lung adenocarcinoma models (41,42). Interestingly, a recent clinical phase 3 study (IMpassion130) assessing the efficacy and safety of atezolizumab (anti-PD-L1 antibody) plus nab-paclitaxel (chemotherapy) in patients with unresectable, locally advanced or metastatic triple-negative breast cancer (TNBC) reported a clinically meaningful overall survival benefit with chemoimmunotherapy in patients with PD-L1 immune cell-positive disease (43).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, our study showed an enhanced efficacy of anti-PD-1 administration plus DOX chemotherapy in reducing the growth in PyMT tumors compared to monotherapy. In line with our findings, preclinical studies demonstrated the efficacy of anti-PD-(L)1 plus different chemotherapy agents in murine colon and lung adenocarcinoma models (41,42). Interestingly, a recent clinical phase 3 study (IMpassion130) assessing the efficacy and safety of atezolizumab (anti-PD-L1 antibody) plus nab-paclitaxel (chemotherapy) in patients with unresectable, locally advanced or metastatic triple-negative breast cancer (TNBC) reported a clinically meaningful overall survival benefit with chemoimmunotherapy in patients with PD-L1 immune cell-positive disease (43).…”
Section: Discussionsupporting
confidence: 90%
“…There is evidence that CCTs can selectively target immune suppressive cell populations, for example preferential depletion of Tregs in response to paclitaxel (82), cyclophosphamide (83), or temozolomide (84) treatment. MDSCs have been shown to be preferentially depleted by doxorubicin (85, 86) and 5-FU (85), and TAMs by gemcitabine (9). CCTs can also activate NK cells (87), but also concurrently render tumor cells more susceptible to NK cell-mediated lysis, such as through promoting the expression of B7-H6, the ligand for the NK cell activating receptor NKp30, on the tumor cell surface (88).…”
Section: The Response Of the Stromamentioning
confidence: 99%
“…Checkpoint blockers remain active systemically for several months beyond the time of administration owing to a half-life of 15-25 days [23-25]; side effects of CBT have been seen up to a year after discontinuation [26]. Murine studies suggest that chemotherapy increases the antitumor activity mediated by CBT by inducing immunological changes, which vary depending on the chemotherapeutic agent used [27]. In lung cancer and renal cell carcinoma, the addition of immunotherapy to chemotherapy and targeted agents has shown superior results to chemotherapy alone [28,29].…”
Section: Number Of Patientsmentioning
confidence: 99%